Educação escolar indígena na comunidade de Querari: práticas pedagógicas e desafios no contexto de fronteira Brasil-Colômbia - Lana, Franz Rodrigues (Universidade Federal de São Carlos, 2026)
Indigenous school education constitutes an important instrument for the valorization of cultural identities, the preservation of traditional knowledge, and the guarantee of educational rights of Indigenous peoples. In this context, the present study aimed to analyze the pedagogical practices and challenges of Indigenous school education in the Querari community, belonging to the Kubeo people, located in the Alto Uaupés region, on the border between Brazil and Colombia. The research sought to understand how the educational practices developed at the Nossa Senhora da Imaculada Conceição Indigenous State School articulate traditional knowledge with school knowledge, considering the territorial, cultural, and social specificities of the community. Methodologically, this is a qualitative research with an exploratory and descriptive character, developed through bibliographic and documentary research. The theoretical framework was based on studies on Indigenous school education, interculturality, territoriality, pedagogical practices, and the sociocultural organization of Indigenous peoples in the Amazon, drawing on works by authors such as Gersem Baniwa, Clarice Cohn, Vera Maria Candau, Catherine Walsh, Rogério Haesbaert, Milton Santos, Diego Pedroso, and other researchers on the subject. The results showed that the Indigenous school plays an essential role in preserving the language, collective memory, and traditional knowledge of the Kubeo people, establishing itself as a space for strengthening cultural identity and building an intercultural education. Challenges were also identified related to geographic isolation, infrastructure limitations, difficulties in accessing public policies, and the need for greater appreciation of pedagogical practices grounded in traditional knowledge. It is concluded that Indigenous school education in Querari constitutes a space for cultural resistance, knowledge production, and territorial strengthening, contributing to the education of new generations without breaking with the values, culture, and identity of the Kubeo people.
Indigenous school education in the Querari community: pedagogical practices and challenges in the context of the Brazil-Colombia border
Keywords: Educação indígena; Kubeo people; Território; Indigenous education; Povo Kubeo; Territory; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA POLITICA; 4. Educação de Qualidade